Antimicrobial Peptides: Amphibian Host Defense Peptides - Patočka, Jiří; Nepovimová, E.; Klímová, B.; Wu, Q.; Kuča, K. (Bentham Science Publishers Ltd., 2019)
Antimicrobial peptides (AMPs) are one of the most common components of the innate immune system that protect multicellular organisms against microbial invasion. The vast majority of AMPs are isolated from the frog skin. Anuran (frogs and toads) skin contains abundant AMPs that can be developed therapeutically. Such peptides are a unique but diverse group of molecules. In general, more than 50% of the amino acid residues form the hydrophobic part of the molecule. Normally, there are no conserved structural motifs responsible for activity, although the vast majority of the AMPs are cationic due to the presence of multiple lysine residues; this cationicity has a close relationship with antibacterial activity. Notably, recent evidence suggests that synthesis of AMPs in frog skin may confer an advantage on a particular species, although they are not essential for survival. Frog skin AMPs exert potent activity against antibiotic-resistant bacteria, protozoa, yeasts, and fungi by permeating and destroying the plasma membrane and inactivating intracellular targets. Importantly, since they do not bind to a specific receptor, AMPs are less likely to induce resistance mechanisms. Currently, the best known amphibian AMPs are esculentins, brevinins, ranacyclins, ranatuerins, nigrocin-2, magainins, dermaseptins, bombinins, temporins, and japonicins-1 and -2, and palustrin-2. This review focuses on these frog skin AMPs and the mechanisms underlying their antimicrobial activity. We hope that this review will provide further information that will facilitate further study of AMPs and cast new light on novel and safer microbicides.
Keywords: Antimicrobial peptide; AMPs; antibacterial; amphibian defense peptides; esculentins; brevinins; ranacyclins; ranatuerins.